2022
DOI: 10.3390/cancers14081945
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of Colorectal Cancer

Abstract: In this review, the mechanobiology of colorectal cancer (CRC) are discussed. Mechanotransduction of CRC is addressed considering the relationship of several biophysical cues and biochemical pathways. Mechanobiology is focused on considering how it may influence epithelial cells in terms of motility, morphometric changes, intravasation, circulation, extravasation, and metastization in CRC development. The roles of the tumor microenvironment, ECM, and stroma are also discussed, taking into account the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 199 publications
0
8
0
Order By: Relevance
“…Altogether, our findings shed light on the regulation of cell fate transitions underlying CRC metastasis and provide novel insights into the role of mechanosensitive calcium channels in tumor malignancy. Future studies may delineate whether other pro-metastatic processes influenced by calcium influx contribute to the mechanical regulation of CRC progression (Monteith et al, 2017), and how integrins and mechanosensitive channels interact with other force-sensitive mechanisms that may impact intestinal tumors (Brás et al, 2022; Broders-Bondon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our findings shed light on the regulation of cell fate transitions underlying CRC metastasis and provide novel insights into the role of mechanosensitive calcium channels in tumor malignancy. Future studies may delineate whether other pro-metastatic processes influenced by calcium influx contribute to the mechanical regulation of CRC progression (Monteith et al, 2017), and how integrins and mechanosensitive channels interact with other force-sensitive mechanisms that may impact intestinal tumors (Brás et al, 2022; Broders-Bondon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The BM is primarily composed of laminin and collagen IV and serves as a structural barrier to cancer cell invasion, intravasation, and extravasation. Cancer invasion through the BM is the initial stage of tumor dissemination and metastasis [24][25][26]. In epithelial cancers, cells must penetrate the BM to metastasize.…”
Section: Basement Membrane and Extracellular Matrixmentioning
confidence: 99%
“…Recent studies indicate protease-independent BM invasion through physical forces generated by cancer cells, involving collective cellular interactions, proliferation, CAFs, and myoepithelial and immune cells. In this hypothesis, disruption of the BM, like metastasis, involves the cells pushing through the basement membrane into the stoma [26,31]. The ability of tumor cells to form various types of actin-rich protrusions, including invasive protrusions (invadopodia) and locomotor protrusions (lamellipodia [2D] or pseudopodia [3D]), may play an important role in BM disruption and tumor cell dissemination [26,32] (see below).…”
Section: Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Their results have shown that living cells tend to possess different mechanobiological properties, including viscosity and stiffness, when affected by diseases like cancer, and variations in these properties have been proposed as biomarkers for early-stage detection. 10 , 103 …”
Section: Existing Diagnostic Techniquesmentioning
confidence: 99%